Evaluating the Role of Transparent Financial Reporting on Capital Structure Decision-Making of Nigerian Beverage Companies - Olaoye, Ayoola Azeez (Universitas Kristen Maranatha, 2024)
Purpose – Inaccurate financial report may lead to wrong financing decisions in a business. This study therefore examines how financial reporting transparency supports the capital structure decisions-making process, focusing on Nigerian listed beverage companies. Design/methodology/approach – The study analyzes secondary data from the annual financial statements of six selected listed beverage firms for a period of twelve years (2012- 2023). The research employs an ex post facto research approach. The research applies descriptive statistics and panel regression methods comprising fixed effect, random effect and pooled least squares models. After conducting model selection tests, the study considers a random effect model for data estimation. Findings – The results reveal that capital adequacy, debt financing and tangibility of asset play positive significant roles on capital structure decisions-making of Nigerian beverages companies. The research discovers that maintaining transparent financial reports facilitate capital structure decision-making processes of Nigerian beverage companies. The study suggests for beverage firms to diversify their financing sources in order to reduce dependency on debt and avoid its associated risks Research limitations/implications – The limitations include industry specificity and regional applicability, but the findings highlight the importance of adequate capital, tangible assets and debt financing in capital structure decision of beverage companies. Keywords: Capital Structure, Decision-Making, Nigerian Beverage Companies, Transparent Financial Reporting